2021
DOI: 10.1016/j.mgene.2021.100910
|View full text |Cite
|
Sign up to set email alerts
|

Design of advanced siRNA therapeutics for the treatment of COVID-19

Abstract: COVID-19 is a newly emerged viral disease that is currently affecting the whole globe. A variety of therapeutic approaches are underway to block the SARS-CoV-2 virus. Among these methods, siRNAs could be a safe and specific option, as they have been tested against other viruses. siRNAs are a class of inhibitor RNAs that act promisingly as mRNA expression blockers and they can be designed to interfere with viral mRNA to block virus replication. In order to do this, we designed and evaluated the efficacy of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Several other in silico studies predicted siRNAs targeting ORF1ab [48][49][50][51], S gene [49,[51][52][53], ORF3 [49,51], E gene [49], M gene [49,51] and N gene [51,53] of SARS-CoV-2. Two in vitro studies further demonstrated a robust downregulation of S, M and N on the mRNA or protein levels by siRNAs in overexpression cell culture models [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Several other in silico studies predicted siRNAs targeting ORF1ab [48][49][50][51], S gene [49,[51][52][53], ORF3 [49,51], E gene [49], M gene [49,51] and N gene [51,53] of SARS-CoV-2. Two in vitro studies further demonstrated a robust downregulation of S, M and N on the mRNA or protein levels by siRNAs in overexpression cell culture models [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors need to be considered to improve the effectiveness of siRNAs. Firstly, their binding targets should be highly conserved to decrease the possibility of viral escape caused by viral evolution [ 91 ]. For the treatment of SARS-CoV-2 infection, it is suggested that siRNA therapeutics that target the highly conserved region of SARS-CoV-2 could be effective [ 35 ].…”
Section: Sirna Therapy—a Potential and Promising Antiviral Therapeuticmentioning
confidence: 99%
“…Another study designed and evaluated the functions of six siRNAs with increased specificity. These siRNAs could combine SARS-CoV-2 mRNA targets, inducing greater inhibition of viral replication and reduced off-target effects ( Table 1 ) [ 91 ]. In addition, bioinformatics-based methods were also used to design siRNA targeting SARS-CoV-2 RdRp as a therapeutic agent [ 101 ].…”
Section: Sirna Therapy—a Potential and Promising Antiviral Therapeuticmentioning
confidence: 99%
“…Several siRNAs developed for the SARS-COV virus could potentially be used against SARS-COV-2 ( Table 1 ). However, six designed siRNAs for most of the virus mRNAs (siRNA 1, siRNA 2, siRNA 3, siRNA 4, siRNA 5, and siRNA 6) were reported to have a fair but less than acceptable level of proliferation inhibition [ 168 ].…”
Section: Covid-19 Nucleic Acid-based Therapeuticsmentioning
confidence: 99%